Legal Positivism, AI, and the Modern Legal Landscape: Challenges in Education, Research, and Practice - Agnė Juškevičiūtė-Vilienė (Acta Universitatis Lodziensis Folia Iuridica)
In a world that is constantly evolving and modernising, new technologies and automation mean rapid progress in many areas of society, including law. This article aims to discuss whether artificial intelligence will have an impact on legal positivism by influencing the legal profession. This study will first discuss the foundations of legal positivism and the reasons for its crisis and criticism. It will then explore how AI is influencing legal education, research, and legal practice. Finally, it will draw conclusions and indicate how AI is affecting the development of positivism or the stagnation of this legal theory.